Preliminary investigation of the effect of non-cardiac surgery on intraoperative islet and renal function: a single-center prospective cohort study - Sun, Yongtao; Zhang, Xiaoning; Zhang, Min; Guo, Yongle; Sun, Tao; Liu, Mengjie; Gao, Xiaojun; Liu, Yang; Gao, Zhongquan; Chen, Lina; Du, Xiaoyan; Wang, Yuelan (Frontiers in Medicine, 2024)
Background The effect of different non-cardiac surgical methods on islet and renal function remains unclear. We conducted a preliminary investigation to determine whether different surgical methods affect islet function or cause further damage to renal function. Methods In this prospective cohort study, the clinical data of 63 adult patients who underwent non-cardiac surgery under general anesthesia were evaluated from February 2019 to January 2020. Patients were divided into the abdominal surgery group, the laparoscopic surgery group, and the breast cancer surgery group. The primary outcome was the difference between the effects of different surgical methods on renal function. Results Islet and renal function were not significantly different between the groups. The correlation analysis showed that hematocrit (HCT) and hemoglobin (HB) were negatively correlated with fasting plasma glucose (FPG) (p < 0.05), MAP was positively correlated with C-peptide (p < 0.05), and HCT and Hb were positively correlated with serum creatinine (SCr) (p < 0.05). Fasting insulin (FINS) and C-peptide were negatively correlated with SCr (p < 0.05), and the homeostatic model assessment of insulin resistance (HOMA-IR) was positively correlated with SCr (p < 0.05). FINS, C-peptide, HOMA-IR, and the homeostatic model assessment of β-cell function (HOMA-β) were positively correlated with cystatin C (Cys C) (p < 0.05). Conclusion FINS, C-peptide, and HOMA-IR had positive effects on beta-2-microglobulin (β2-MG). FINS, C-peptide, and HOMA-IR were positively correlated with Cys C and β2-Mg. While FINS and C-peptide were negatively correlated with SCr, HOMA-IR was positively correlated with SCr.